Identification of a Noncanonical Signal for Transcription of a Novel Subgenomic mRNA of Mouse Hepatitis Virus: Implication for the Mechanism of Coronavirus RNA Transcription - Zhang, Xuming (Virology, 2000)
Subgenomic RNA transcription of coronaviruses involves the interaction between the leader (or antileader) and the intergenic (IG) sequences. However, it is not clear how these two sequences interact with each other. In this report, a previously unrecognized minor species of subgenomic mRNA, termed mRNA5–1, was identified in cells infected with mouse hepatitis virus (MHV) strains JHM2c, JHM(2), JHM(3), A59, and MHV-1. Sequence analysis revealed that the leader-body fusion site of the mRNA is located at approximately 150 nucleotides (nt) downstream of the consensus IG sequence for mRNA 5 and did not have sequence homology with any known IG consensus sequences. To determine whether this sequence functions independently as a promoter, we cloned a 140-nt sequence (from ≈70 nt upstream to ≈70 nt downstream of the fusion site) from viral genomic RNA and placed it in front of a reporter gene in the defective-interfering (DI) RNA-chloramphenicol acetyltransferase (CAT) reporter vector. Transfection of the reporter RNA into MHV-infected cells resulted in synthesis of a CAT-specific subgenomic mRNA detected by reverse transcription-polymerase chain reaction (RT-PCR). The strength of this promoter was similar to that of the IG7 (for mRNA 7) as measured by the CAT activity. Deletion analysis showed that the sequence as few as 13 nt was sufficient to initiate mRNA transcription, while mutations within the 13-nt abolished mRNA transcription. In vitro translation study confirmed that the envelope (E) protein was translated from mRNA5–1, which encodes the open reading frame (ORF) 5b at its 5′-end, indicating that mRNA5–1 is a functional message. Furthermore, when the ORF5b was replaced with the CAT gene and placed in the DI in the context of viral mini-genome, CAT was expressed not only from the first ORF of mRNA5–1 but also from the second and third ORF of mRNA5 and genomic DI RNA, respectively, suggesting that more than one mechanism is involved in regulation of ORF5b expression. Our findings thus support the notion that base-pairing between the leader (or antileader) and the IG is not the sole mechanism in subgenomic RNA transcription.